Examining The Impact of Parental Involvement On Preschooler's Early Learning: A Case Study at The ECCE Demonstration Centre in Jigawa State College of Education and Legal Studies Ringim (British Journal of Multidisciplinary and Advanced Studies, 2024)
This research examines the influence of parental involvement on the early learning experiences of preschoolers in the ECCE Demonstration School at Jigawa State College of Education and Legal Studies. Through a case study approach, we investigate the various forms of parental involvement and their effects on children's academic, social, and emotional development. Data were collected using surveys, interviews, and observations involving parents, teachers, and preschoolers and analyzed to identify patterns and themes related to parental involvement and its impact. Our findings reveal that active parental involvement significantly enhances preschoolers' early learning experiences. Home-based activities, communication with teachers, and participation in school events emerge as crucial aspects of parental involvement that positively influence children's cognitive development, social skills, and emotional well-being. The study underscores the critical role of parental involvement in early childhood education. Educators, parents, and policymakers should recognize the importance of fostering strong home-school partnerships to better support the holistic development of preschoolers and lay a solid foundation for their future educational journey.